A GENEALOGICAL RECONSTRUCTION OF LUBUKUSU, LUMASABA AND LUGISU - Lwangale, David Wafula (IJRDO-Journal of Applied Science, 2015)
A genealogical study is aimed at establishing a historical relationship among languages. The study at hand focused on the genealogical relationship that runs across Lubukusu, Lugisu, and Lumasaba. The presumption that classification of Luluhyia language was incomplete provided the basis of the study and a comparative reconstruction of a proto-language for Lubukusu, Lumasaba and Lugisu was done. Random and stratified sampling procedure became very instrumental in sample selection of informants and word forms. Data collection was done through oral interviews as well as use of questionnaires. Data analysis and interpretation was by use of descriptive statistics specifically proportion percentages and means. The research confirmed its objectives to be valid, that is, established that Lugisu and Lumasaba are dialects of Luluhyia language and successful attempt of “protomundu” reconstruction was done. Thus, the claim that Lubukusu, Lugisu, and Lumasaba are of common descent and that they are all dialects of Luluhyia language is true.